EVALUASI KEBIJAKAN PERKAWINAN PADA USIA ANAK DI KABUPATEN BOJONEGORO - Pramesti Nugroho, Anindya; Lituhayu, Dyah; Larasati Setianingsih, Endang (Journal of Public Policy and Management Review, 2024)
A marriage is considered valid if it has the consent of both parents. This article has given rise to many practices of dispensation for underage marriages in Bojonegoro Regency which violate state regulations for marrying under the age requirement. The aim of this research is to determine the process of implementing the Child Marriage policy in Bojonegoro Regency and to determine the Encouraging and Inhibiting Factors in the Implementation of the Child Marriage Policy in Bojonegoro Regency. The method used in this research is descriptive qualitative with data collection techniques through interviews, observation, documentation and literature study. The research results show that the child marriage policy is in accordance with the law and has also been implemented well, however there are still several obstacles in several factors and indicators contained in the policy evaluation assessment criteria, there are programs that are deemed inappropriate because they only provide treatment. temporary, not on long-term goals. Thus, there are six evaluation criteria that achieve maximum results, namely the criteria for effectiveness, efficiency, adequacy, responsiveness and program accuracy. However, the equality criteria have not shown maximum results due to differences in society's perspective based on local cultural habits, therefore by strengthening the government's efforts in conducting outreach and guidance to parents to form an understanding of the impact of child marriage, the complexity of the aspects that need to be prepared at the level marriage, health, and negative impacts. Apart from that, the government needs to strengthen the role of parents in supervising children, both from their social environment and their use of social media. Several programs can be utilized by OPD to shape behavior in accordance with the 2019 Marriage Law, namely PUP (Marriage Age Maturation).